Airfield Asphalt Overlay Design for Non-conventional Pavement Structures: A Case Study of Airport in Indonesia - Taqia Rahman; Bambang Suhendro; Wardhani Sartono; Purbolaras Nawangalam; Hary Christady Hardiyatmo (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2022)
Airfield pavements begin a gradual deterioration from several sources, including traffic load and environmental conditions. To achieve its intended design life, routine maintenance, repair, and rehabilitation should be performed. There are considerable research and studies conducted on the design and practice of pavements rehabilitation/overlay for typical airfield pavements. However, most of the existing guidelines and studies are only suitable for pavements with conventional structures. There has been no detailed investigation into the practice of airfield asphalt overlay for non-conventional pavement structures, such as chicken claw /Cakar Ayam pavement system and nailed-slab system. In the present article, challenges and issues for airfield asphalt overlay design for non-conventional pavement structures were examined based on an actual runway rehabilitation project in one of the major airports in Indonesia in 2015. The overlay design procedure, the evaluation of the existing pavement condition, including visual surveys and deflection tests, and the pre-overlay treatments were also discussed. In addition, a finite element (FE) simulation to model the non-conventional pavement structure was developed to calculate the required overlay thickness. The result showed that, during the overlay design of non-conventional pavement structure, data from falling weight deflectometer (FWD) could not be directly used to estimate the back-calculated layers moduli because of the difference in the geometric features of the pavement structure. Moreover, the FE model can be a robust tool to simulate the complex three-dimensional geometric features of a non-conventional pavement and important loading conditions, such as interface shear bond of overlay, that are usually not available in other tools, such as FAARFIELD. Finally, this study showed that the additional asphalt overlay could reduce the fatigue stress at the bottom of the existing slab and vertical stress at the top of the subgrade, resulting in overall smaller stress levels